ANÁLISE MULTITEMPORAL DA TEMPERATURA SUPERFICIAL NA PRODUÇÃO DO CLIMA URBANO EM TRÊS LAGOAS-MS - DIOGO CERDAN BRITO (2025)
The multi-temporal study of urban climate, focused on surface temperature, carried out in this research, presupposes the articulation between the production of urban space and the production of an urban climate in the research area. The aim of this work is to analyze the formation of an urban climate in Três Lagoas-MS in the years 2013, 2018 and 2023, based on the process of expansion of the urban network and the analysis of local thermal characteristics. To this end, it was necessary to address and analyze the urban expansion of the city in the time frame of the analysis; to ascertain the surface temperatures in our space-time frame; to identify the use and occupation of the land in the proposed period and space; and to identify whether there is a relationship between urban expansion and changes in the local urban climate. The methodology of the work is based on the theoretical-methodological proposal of the Urban Climate System (UCS) by Monteiro (1976). Thermal maps, maps of the Normalized Difference Vegetation Index (NDVI), land use and occupation, hypsometry, declivity and slope orientation were drawn up to characterize the urban and geoecological aspects of the study area, and then analyzed. The data obtained was analyzed on a multi-temporal basis in two areas: from the new built-up areas resulting from urban expansion in the process of producing space, at five points of analysis; and from the areas in which surface heat islands formed in the urban area of Três Lagoas in the year 2023, identifying the intensity of the islands, at four points of analysis. Most of the points analyzed in the new built-up areas showed an increase in surface temperature between 2013 and 2023, with the exception of one point, and also that as the surface temperature increased, the NDVI fell. With regard to the areas where surface heat islands occurred in 2023, the highest surface temperatures predominated in areas of low vegetation and/or exposed soil, on the edges of the urban area, with the intensity of the surface heat islands at the analysis points varying between 10 and 10,4 °C in relation to the area of dense vegetation used as a comparative parameter. Finally, when thinking about the urban climate of a city, it is extremely important to take into account the unequal way in which it is experienced by the different social classes that make up the city, as well as their unequal possibilities for dealing with the temperatures that affect the urbanized space.